Proyecto a nivel de ejecución de laboratorios de la facultad de agronomía – UNSM - Colichon Romero, Jorge Antonio (1996)
City University, National University of San Martin, located in the Morales District of San Martin region, is in the process of implementing infrastructure to achieve compliance with their academic goals and research that will help in the Socio-Economic Development Regional.  Physical development is subject to the management of the General Planning Office through the Office of Infrastructure conllevada same execution mode for direct administration. This thesis is to contribute to the development of a naconal University of St. Martin and while consolidating knowledge during the study of the career of civil engineering, allowing me to have evidence for the development of this and other projects. This study has been accepted as a thesis topic by the faculty of civil engineering obtar title of civil engineer, being developed comprehensively and whose complementary themes are sequentially described in each chapter